The paratexts of the translations into Spanish of E. M. Forster’s A Passage to India - Alonso-Gómez, Marina (My University, 2018)
In this paper will focus on the peritexts of the translations into Spanish of a novel by British author E. M. Forster, A Passage to India. The novel first appeared in 1924 and it has been translated into Spanish three different times: first in 1955 by Juan Rodolfo Wilcock for an Argentinian publishing house, Sur; then in 1981 by José Luis López Muñoz for an Spanish publishing house, Alianza; and finally in 2004 by Juan Gabriel Vásquez for a collection of travel books commissioned by a Spanish newspaper, ABC.
Keywords: Forster, E. M. A Passage to India - Traducciones al español; Traducciónj; Paratexto